2020
DOI: 10.1002/wer.1388
|View full text |Cite
|
Sign up to set email alerts
|

The destruction of Escherichia coli adhered to pipe surfaces in a model drinking water distribution system via various antibiofilm agents

Abstract: The aim of the study is to estimate the effectiveness of three antibiofilm agents against Escherichia coli biofilm that formed in six different types of pipelines. A laboratoryscale water system was built for this work to allow for the creation of biofilm in the pipelines studied. The level of the growth rate of E. coli biofilm cells was monitored over 90 days on those tested pipe materials. The results of bacterial cell densities displayed that the highest biofilm growth was observed in the biofilm formed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…They achieved 4–6 logs of bacterial removal after 180 min using the electrooxidation reactor with two boron-doped diamond and stainless-steel electrodes at the current density of 50 A/m 2 . Correspondingly, the results proved that electro-oxidation is significantly more effective than chemical disinfection using chlorine, where chlorination requires longer exposure (at least 30 min) to achieve a bactericidal performance of 99.94% or higher 19 . Time is essential in designing a disinfection technique related to power and chemical consumption and capital construction 13 .…”
Section: Resultsmentioning
confidence: 76%
“…They achieved 4–6 logs of bacterial removal after 180 min using the electrooxidation reactor with two boron-doped diamond and stainless-steel electrodes at the current density of 50 A/m 2 . Correspondingly, the results proved that electro-oxidation is significantly more effective than chemical disinfection using chlorine, where chlorination requires longer exposure (at least 30 min) to achieve a bactericidal performance of 99.94% or higher 19 . Time is essential in designing a disinfection technique related to power and chemical consumption and capital construction 13 .…”
Section: Resultsmentioning
confidence: 76%
“…32,55,56 Biofilm biomass reduction after chlorination Pipe materials could affect the chlorination effect. 14 Fig. 6 presents the biofilm biomass reduction rate after chlorination.…”
Section: Eps Contents In the Biofilmmentioning
confidence: 99%
“…Among them, Sphingomonas of the α-Proteobacteria and Acinetobacter of the γ-Proteobacteria (ammonia-producing bacteria), 18,19 Acidovorax of the β-Proteobacteria and Microbacterium of Actinobacteria (iron-oxidizing bacteria), 20,21 and Bacillus of the Bacilli (iron-reducing bacterium) 22 may cause iron pipe corrosion. Moreover, it has also been reported that the effect of chlorine may be worse in some pipes 14,23 because some pipe materials may react with disinfectants. 24,25 However, as different typical bacterial strains, pipe materials, and incubation conditions could lead to inconsistent or even contradictory conclusions, it is important to study the effects of biofilm formation in DWDSs by selecting multiple representative bacterial strains and consistently maintaining the incubation conditions for multiple pipe materials.…”
Section: Introductionmentioning
confidence: 99%
“…After that, the plankton was removed, and the wells were washed with PBS to remove non-adherent bacteria. The crystal violet (CV) assay performed as described in detail elsewhere [25].…”
Section: Examination Of Antibio Lm Activitiesmentioning
confidence: 99%